Draft Annual Plan 1986-87 Seventh Five Year Plan 1985-90 Government of Pondicherry - Planning Commission (Planning Commission, 1985)
Spill over works in continuing Schemes Construction (in phased manner) of 175 residential quarters, 10 Police station buildings with ancillary buildings and acquisition of lands.
Government of Pondicherry, Planning and Research Department